2020
DOI: 10.1186/s12889-020-08977-y
|View full text |Cite
|
Sign up to set email alerts
|

Covert use of contraception in three sub-Saharan African countries: a qualitative exploration of motivations and challenges

Abstract: Background: The balance between increasing men's participation in family planning and rights-based initiatives favoring women's empowerment is highlighted with the issue of covert use of contraception. While covert use has been documented in low-and middle-income countries as a way for women to obtain contraception in light of partner opposition, little is known about women's decision-making processes, actions, and potential consequences of discreet contraceptive use. We aimed to understand women's choices to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 37 publications
6
91
0
1
Order By: Relevance
“…When couples negotiate reproductive outcomes, this is done against the backdrop of normative values, and if they disagree, whether this is real or perceived, there needs to be some form of conflict resolution [6]. As a result of the outcome of couple communication, or the absence of any communication, women may decide on their own to use a family planning method, even if this means using a method covertly [2,5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When couples negotiate reproductive outcomes, this is done against the backdrop of normative values, and if they disagree, whether this is real or perceived, there needs to be some form of conflict resolution [6]. As a result of the outcome of couple communication, or the absence of any communication, women may decide on their own to use a family planning method, even if this means using a method covertly [2,5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a man's suspicion that his partner is using a contraceptive method covertly may be raised due to side effects, such as heavy bleeding, weight gain or loss, and lack of libido, or due to a delay in her becoming pregnant. Such suspicions, and the tension they cause may lead to disclosure by some women, ultimately bringing about improvement in communication between partners [10]. On the other hand, it has been reported that if a male partner discovers on his own that a woman is using a method without his approval, he may feel betrayed [5,10] and could report her to her parents, accuse her of infidelity, stop having sex with her, start an extramarital affair, physically abuse her, marry another wife, withdraw economic support, or even divorce her, all in a bid to "punish" and "disgrace" her for her actions [5,[8][9][10]12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the study in Ghana included both married and unmarried women using contraceptives [28]. The practice of CCU could be due to societal perception of women using contraceptive as being promiscuous [6,14,28,29], patriarchy [9,29], fear of intimate partner violence [13,30,31], disagreement on the number of children [29], religious beliefs [14] and limited male involvement [6,32]. CCU could re ect women empowerment and autonomy in decision making [31] but could also indicate male dominance in decision making and create a barrier to increasing contraceptive coverage [9].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies in Ethiopia [27], Ghana [28], Kenya [1,15] and Nigeria [5], injectables and implants were the commonest methods of contraceptives used overtly and covertly by married women. Injectables and implants are easy-to-use, effective, concealable [31], modern reversible contraceptives lasting three months, and three or ve years, respectively [3]. Injectables are also widely available and accessible in most health facilities and pharmacies hence promote CCU [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation